Analysis of microdeletions in 22q11 in Colombian patients with congenital heart disease (2011)
Cardiac defects are the most frequent congenital malformations, with an incidence estimated between 4 and 12 per 1000 newborns. Their etiology is multifactorial and might be attributed to genetic predispositions and environmental factors. Since 1990 these types of pathologies have been associated with 22q11 microdeletion. In this study, the frequency of microdeletion 22q11 was determined in 61 patients with non-syndromic congenital heart disease. DNA was extracted from peripheral blood and TUPLE1 and STR D10S2198 genes were amplified by multiplex PCR and visualized in agarose gels. Gene content was quantified by densitometry. Three patients were found with microdeletion 22q11, representing a 4.9% frequency. This microdeletion was associated with two cases of Tetralogy of Fallot and a third case with atrial septal defect (ASD). In conclusion, the frequency for microdeletion 22q11 in the population analyzed was 4.9%. The cases that presented Teratology of Fallot had a frequency for this microdeletion of 7.4% and for ASD of 11.1%.